Evaluation of Serum Biomarkers and Other Diagnostic Modalities for Early Diagnosis of Preeclampsia - Angela Felicia Sunjaya; Anthony Paulo Sunjaya (Tehran University of Medical Sciences, 2019)
Objective: Preeclampsia (PE) is a multi-systemic complication of pregnancy often characterised with the onset of hypertension and proteinuria after 20 weeks of gestation. Today, PE is the leading cause of maternal and perinatal morbidity and mortality worldwide. An early detection of PE would allow a chance to plan the appropriate monitoring and for clinical management to be immediately done following early detection thus making prophylactic strategies much more effective. Materials and methods: This systematic review aims to evaluate the potential of the various serum biomarkers and diagnostic modalities (uterine artery Doppler, MAP, and maternal history) available for early prediction of PE with articles included and obtained through MEDLINE Full Text, Pubmed, Science Direct, ProQuest, SAGE, Taylor and Francis Online, Google Scholar, HighWire and Elsevier ClinicalKey. Results: Ninety-five articles were found that fulfilled all of our inclusion criteria. Placental growth factor (PlGF), pregnancy associated plasma protein A (PAPP-A), soluble fms-like tyrosine kinase (sFLT) and placental protein 13 (PP-13) were the most commonly studied biomarkers. Whereas uterine Doppler scanning and Mean Arterial Pressure (MAP) were the most commonly studied out of other modalities. Conclusion: Current evidence shows serum biomarkers such as PIGF, PP-13 and sFlt yielded the best results for a single biomarker with others having conflicting results. However, a combination model with other diagnostic modalities performed better than a single biomarker. In the future, new techniques will hopefully provide sets of multiple markers, which will lead to a screening program with clinically relevant performance. However further studies are required to improve current methods.